Analysis of Behavioral Intention to Use Sap S/4hana In Accounting Application Practice Learning Using Utaut Model - Rizki Dwi Putra (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The objectives of this quantitative research are to analyze and gain empirical evidence regarding the effects of performance expectancy, effort expectancy, social influence, facilitating conditions, self-efficacy, and online access convenience on the behavioral intention to use SAP S/4HANA. The population consists of 419 undergraduate accounting students of the Faculty of Economics and Business batch of 2020, 2021, and 2022. Using purposive sampling, 205 students were selected as the respondents, to whom questionnaires were distributed to acquire the primary data. The results of the analysis using PLS-SEM in SmartPLS version 4.0 indicate that performance expectancy, social influence, facilitating conditions, and online access convenience positively and significantly influence the behavioral intention to use SAP S/4HANA. In contrast, effort expectancy and self-efficacy do not positively and significantly affect the said behavioral intention.